The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3109/10717544.2014.992497
|View full text |Cite|
|
Sign up to set email alerts
|

DNA-based vaccination against hepatitis B virus using dissolving microneedle arrays adjuvanted by cationic liposomes and CpG ODN

Abstract: DNA vaccines are simple to produce and can generate strong cellular and humoral immune response, making them attractive vaccine candidates. However, a major shortcoming of DNA vaccines is their poor immunogenicity when administered intramuscularly. Transcutaneous immunization (TCI) via microneedles is a promising alternative delivery route to enhance the vaccination efficacy. A novel dissolving microneedle array (DMA)-based TCI system loaded with cationic liposomes encapsulated with hepatitis B DNA vaccine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 24 publications
(25 reference statements)
1
47
0
Order By: Relevance
“…vaccination with a much lower dose of DNA, due to the inability to deliver 100 % of the DNA cargo from the dissolving MN tips. This suggests that not only does the developed MN delivery system successfully induce an antigen-specific immune response in this animal model but it also has the advantage of being a dose-sparing delivery system [56].…”
Section: Via Dissolving Mn Arraysmentioning
confidence: 98%
See 1 more Smart Citation
“…vaccination with a much lower dose of DNA, due to the inability to deliver 100 % of the DNA cargo from the dissolving MN tips. This suggests that not only does the developed MN delivery system successfully induce an antigen-specific immune response in this animal model but it also has the advantage of being a dose-sparing delivery system [56].…”
Section: Via Dissolving Mn Arraysmentioning
confidence: 98%
“…Qiu et al (2015) developed a dissolving microneedle system, fabricated from PVP, encapsulating cationic liposomes loaded with plasmid DNA encoding the middle envelope proteins of hepatitis B virus and adjuvant CpG oligodeoxynucleotide molecules (10 μg of each). The potency of this system for eliciting antigen-specific immune responses was evaluated by comparison to i.m.…”
Section: Via Dissolving Mn Arraysmentioning
confidence: 99%
“…In particular, this kind of MPMAs loaded with hepatitis B virus DNAs could effectively deliver DNA vaccine into skin, inducing effective immune response toward the desired pathway establishing robust immunity against HBV in mouse model. 46 By comparison, Bouwstra's group demonstrated that encapsulation of model antigen OVA into cationic DOTPA/CpG OND-liposomes had a beneficial effect on the quality of the antibody response in mice after intranodal or i.d. immunization via needle injection but, notably, impaird proper delivery of antigen and adjuvant to the lymph nodes when the formulations are administered intra-nasally or transcutaneously at the site pre-treated by metal MAs (4 £ 4 microneedles with a length of 300 mm).…”
Section: Multifunctional Liposomes Constituted Mpmasmentioning
confidence: 99%
“…20,[29][30][31] The stability of inactivated viruses and protein antigens has been established in certain dissolvable microneedle formulations [32][33][34] however, little investigation has been done to determine whether incorporation into dissolvable microneedles has any influence on the stability of DNA or to directly compare the suitability of different polymer matrices to deliver nucleic acid cargo. This is perhaps surprising given that some polymers have been known to form hydrogen bonds with DNA and have been reported to be capable of enhancing gene delivery in their own right.…”
Section: Introductionmentioning
confidence: 99%
“…18 Microneedles can be defined as a series of sharp microprojections, ranging up to 1000 mm in length, which are capable of piercing the outer barrier of the skin, the stratum corneum (SC), to create transient pores to the viable epidermal and dermal layers. 19 Microneedle-mediated DNA vaccines have demonstrated efficacy in mouse models against pathogenic diseases, such as hepatitis B 20 and influenza, 21 and perhaps more impressively against antigen-expressing tumors. 22,23 Initial gene delivery studies focused on applying DNA solutions to the skin, followed by application of solid microneedles, 24,25 however variability in dosing and high wastage of cargo have seen a shift toward the use of coated microneedles.…”
Section: Introductionmentioning
confidence: 99%